Pengalaman Ibu Mengasuh Anak dengan Resiko GPPH - Tri Utami; Elis Hartati (Jurnal Keperawatan Diponegoro, 2012)
Pre-school children with attention-deficit/hyperactivity disorder (ADHD) cannot concern in long time and the attention can be easily distracted. Many parents realize it after the children enter the primary school. The family, especially mother is the closest support system of the children, who can make efforts to minimize the worse symptom and effect in children with ADHD. The purpose of the research was to explore mothers’ experience in doing parenting to the children with risk of ADHD in Semarang. This was a qualitative research with phenomenological approach. The data were collected using in depth interview method to 5 samples chosen by purposive sampling method. This research showed that the implementation of parenting children with risk of ADHD have not used determining rules consistently using the daily activity schedule. In doing parenting children with risk of ADHD, mothers usually use rewards and punishments. The support system for mother showed by emotional, instrumental and appreciation support. The research concluded that the implementation of parenting children with risk of ADHD by mother showed by the way mother determining rules consistently, the using of rewards and punishments which are influenced by the support system